2016
DOI: 10.1021/acsami.5b11205
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrical Networks of Stretchable Conductors with Small Fraction of Carbon Nanotube/Graphene Hybrid Fillers

Abstract: Carbon nanotubes (CNTs) and graphene are known to be good conductive fillers due to their favorable electrical properties and high aspect ratios and have been investigated for application as stretchable composite conductors. A stretchable conducting nanocomposite should have a small fraction of conductive filler material to maintain stretchability. Here we demonstrate enhanced electrical networks of nanocomposites via the use of a CNT-graphene hybrid system using a small mass fraction of conductive filler. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 31 publications
5
86
0
Order By: Relevance
“…demonstrated that in CNT-Graphene-PDMS hybrid fillers, the synergistic effects in the CNTgraphene mixture prevent agglomeration of CNTs and the restacking of graphene to improve electrical performance while maintaining high stretchability [83] (Figure 3c). …”
Section: Mixed-metal Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that in CNT-Graphene-PDMS hybrid fillers, the synergistic effects in the CNTgraphene mixture prevent agglomeration of CNTs and the restacking of graphene to improve electrical performance while maintaining high stretchability [83] (Figure 3c). …”
Section: Mixed-metal Compositesmentioning
confidence: 99%
“…Schematic displays the interaction between CNTs and graphene. Reprinted with permission from [83] . Reprinted with permission from [97] .…”
Section: List Ofmentioning
confidence: 99%
“…26 For other comparison, the electrical conductivity of a pellet of CNTs obtained by compression was only of 10 S cm −1 which is close to the reported value of the macroscopic electrical conductivity of MWCNTs. 24 The relatively low conductivity of the pellet of CNTs compared to the conductivity of one single tube may be imparted to a poor contact between each tube. The pyrolysis appears thus to generate a carbonaceous cement binding the CNTs all together, forming a dense network and therefore promoting good electrical contact.…”
Section: Nanocomposites Preparation and Characterizationmentioning
confidence: 99%
“…For instance, a polydimethylsiloxane matrix is found to reach a conductivity of around 10 −1 S cm −1 in the presence of 5 wt% CNTs. 24 Higher electrical conductivity may be obtained by increasing dramatically the CNT content, up to 50 wt%, entering in this case the area of the so-called buckypapers. For example, Chapertegui et al 25,26 were able to prepare a CNT-Benzoxazine buckypaper showing a very interesting electrical conductivity, close to 30 S cm −1 .…”
Section: From Nanocomposite To Nanohybridmentioning
confidence: 99%
“…Stretchable electrodes are one of the key components of future electronic devices such as flexible and stretchable displays, strain sensors, actuators, nanogenerators, and wearable electronic devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Thus, simple and cost-effective processes for the fabrication of stretchable electrodes will be in high demand.…”
Section: Introductionmentioning
confidence: 99%